Polymer Solar Cells: Strategically Manipulated Polymer Solar Cells to Incorporate Plasmonically Enhanced Spectral Upconversion Backplane (Advanced Optical Materials 16/2020). Issue 16 (19th August 2020) - Cho, Ha‐Eun; Lee, Na‐Kyung; Song, Young Jin; Hong, Jinwook; Kang, Hyelim; Lim, Soo Yeong; Lee, Jaegab; Kim, Hyung Min; Lee, Nohyun; Cho, Seok Ho; Lee, Sung‐Min
Abstract : Nohyun Lee, Seok Ho Cho, Sung‐Min Lee and co‐workers (article number 2000466 ) present a strategic design of polymer solar cells that can incorporate the plasmonically enhanced upconversion backplane. By employing wavelength‐selectively transparent rear electrodes, the photon transmission only at excitation and emission wavelengths of the upconversion process is enabled, thereby achieving the upconversion effect of photocurrent augmentation without compromising pre‐existing levels of the photovoltaic performance.